Recognition Investigation of Community Pharmacists Implementing Good Pharmacy Practice in Korea. (July 2022) - Kim, Dae-Won; Lee, Beom-Jin
This study aimed to verify, for the first time, the need for Good Pharmacy Practice (GPP) regulations as guidelines to provide pharmaceutical care services in community pharmacies in Korea. Statistical analyses were performed with demographic characteristics, institutional factors, and diversity factors of 3 pharmaceutical care services as independent variables and the favorability of GPP implementation as a dependent variable. In assessing the diversity of methods of providing pharmaceutical care services as an indicator of willingness to provide these services, this study understood such diversity as an innovative behavior that represents the efforts and willingness of pharmacists to provide better services. The results of descriptive statistics showed that most pharmacists in community pharmacy recognize that guidelines are necessary to provide better pharmaceutical care services. The statistical correlation analysis results confirmed that a greater need for guidelines was strongly related to higher GPP favorability. The institutional factors had the greatest influence on GPP favorability, rather than diversity factors of pharmaceutical care services, ultimately with the Korean perspectives to equate the GPP with the guidelines for pharmaceutical care services. Our study confirmed that it is a wish and a policy task of community pharmacists in Korea to enact GPP as soon as possible.